Effect of Al2O3 and SiO2 metal oxide nanoparticles blended with POME on combustion, performance and emissions characteristics of a diesel engine - Adzmi, M. A.; Abdul Adam, Abdullah; Abdullah, Z.; Mrwan, Anes G. (Universiti Malaysia Pahang, 2019)
Evaluation of combustion characteristic, engine performances and exhaust emissions of nanoparticles blended in palm oil methyl ester (POME) was conducted in this experiment using a single-cylinder diesel engine. Nanoparticles used was aluminium oxide (Al2O3) and silicon dioxide (SiO2) with a portion of 50 ppm and 100 ppm. SiO2 and Al2O3 were blended in POME and labelled as PS50, PS100 and PA50, PA100, respectively. The data results for PS and PA fuel were compared to POME test fuel. Single cylinder diesel engine YANMAR TF120M attached with DEWESoft data acquisition module (DAQ) model SIRIUSi-HS was used in this experiment. Various engine loads of zero, 7 N.m, 14 Nm, 21 N.m and 28 N.m at a constant engine speed of 1800 rpm were applied during engine testing. Results for each fuel were obtained by calculating the average three times repetition of engine testing. Findings show that the highest maximum pressure of nanoparticles fuel increase by 16.3% compared to POME test fuel. Other than that, the engine peak torque and engine power show a significant increase by 43% and 44%, respectively, recorded during the PS50 fuel test. Meanwhile, emissions of nanoparticles fuel show a large decrease by 10% of oxide of nitrogen (NOx), 6.3% reduction of carbon dioxide (CO2) and a slight decrease of 0.02% on carbon monoxide (CO). Addition of nanoparticles in biodiesel show positive improvements when used in diesel engines and further details were discussed.